2016
DOI: 10.1111/epi.13591
|View full text |Cite
|
Sign up to set email alerts
|

Temporal behavior of seizures and interictal bursts in prolonged intracranial recordings from epileptic canines

Abstract: Objective Epilepsy is a chronic disorder, but seizure recordings are usually obtained in the acute setting. The chronic behavior of seizures and the interictal bursts that sometimes initiate them is unknown. We investigate the variability of these electrographic patterns over an extended period of time using chronic intracranial recordings in canine epilepsy. Methods Continuous, yearlong intracranial EEG recordings from four dogs with naturally occurring epilepsy were analyzed for seizures and interictal bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
(55 reference statements)
3
36
0
Order By: Relevance
“…Another confounding factor in our data is that the surgical implantation itself could artificially alter seizure dynamics. Using chronic recordings of epileptic canines, Ung et al (72) found variability in seizure onset and interictal burst dynamics, with the most stable dynamics emerging approximately a few weeks after electrode implantation. In agreement with their work, we found that earlier seizure evolutions often recurred later in the recording, making it unlikely that gradual changes in the recording quality or an acute reaction to the surgery underlay the observed variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another confounding factor in our data is that the surgical implantation itself could artificially alter seizure dynamics. Using chronic recordings of epileptic canines, Ung et al (72) found variability in seizure onset and interictal burst dynamics, with the most stable dynamics emerging approximately a few weeks after electrode implantation. In agreement with their work, we found that earlier seizure evolutions often recurred later in the recording, making it unlikely that gradual changes in the recording quality or an acute reaction to the surgery underlay the observed variability.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with their work, we found that earlier seizure evolutions often recurred later in the recording, making it unlikely that gradual changes in the recording quality or an acute reaction to the surgery underlay the observed variability. Instead, Ung et al (72) hypothesized that seizure variability results from transient, atypical dynamics as the brain recovers from surgery, with later dynamics representing a truer epileptic network. Other stressors, such as medication withdrawal, could similarly elicit abnormal dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been demonstrated in that seizures can have similar clinical appearance while arising from different parts of an epileptic networks, sometimes with different EEG signatures. A recent study by our group shows this phenomenon in a long-term canine model 46 . Classifying seizures and mapping their temporal trends is an ongoing project in our laboratory.…”
Section: Discussionmentioning
confidence: 52%
“…Temporal variability in seizures and interictal bursts after electrode implantation reach steady state after several weeks, similar to humans, which adds to the translational relevance of this model 62 . The interictal bursts in dogs are tenfold more frequent than seizures, which provides insights into the physiological changes that inhibit transformation of interictal into ictal activity 63 .…”
Section: Epilepsymentioning
confidence: 99%